Figurative Languages Found in Paint My Love Greatest Hits Lyrics - Ratna Putri Krisnisa; Sukarni, Semi; Zulia Chasanah (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
Language is a fundamental tool in communication and expression, including in the realm of music. Songs, as a form of art, often use figurative language to convey messages more emotionally and aesthetically. However, not all listeners are able to understand the hidden meaning behind the lyrics, especially when figurative language is used. This study aims to examine the use of figurative language in the album Paint My Love Greatest Hits by referring to Frederik's theory. This study uses a qualitative approach to analyze the types and meanings of figurative language found in song lyrics. Data were obtained from all songs in the album. The results of the analysis show that the most frequent type of figurative language is symbols (42.86%), while the least frequent are hyperbole, litotes, metonymy, and paradox. These findings reveal that figurative language plays an important role in enriching the meaning and emotional depth of song lyrics.